2020
DOI: 10.3390/jintelligence8030034
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in Judging Others’ Personalities: The Role of Emotion Recognition, Emotion Understanding, and Trait Emotional Intelligence

Abstract: The ability to accurately judge others’ personality and the ability to accurately recognize others’ emotions are both part of the broader construct of interpersonal accuracy (IPA). However, little research has examined the association between these two IPA domains. Little is also known about the relationship between personality judgment accuracy and other socio-emotional skills and traits. In the present study, 121 participants judged eight traits (Big Five, intelligence, cooperativeness, and empathy) in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
2
4
0
Order By: Relevance
“…With respect to demographic variables, we expected a small advantage of women over men in terms of performance, in line with robust findings in emotion recognition (e.g., meta-analyses by Hall, 1978, andVoyer, 2014). There is also accumulating evidence for the same gender difference in personality judgment accuracy (e.g., Letzring, 2008;Vogt & Colvin, 2003;Jaksic & Schlegel, 2020). In addition, we expected the WIPS to be uncorrelated with age.…”
Section: Overview Of the Present Studies And Hypothesessupporting
confidence: 73%
See 2 more Smart Citations
“…With respect to demographic variables, we expected a small advantage of women over men in terms of performance, in line with robust findings in emotion recognition (e.g., meta-analyses by Hall, 1978, andVoyer, 2014). There is also accumulating evidence for the same gender difference in personality judgment accuracy (e.g., Letzring, 2008;Vogt & Colvin, 2003;Jaksic & Schlegel, 2020). In addition, we expected the WIPS to be uncorrelated with age.…”
Section: Overview Of the Present Studies And Hypothesessupporting
confidence: 73%
“…This version was therefore considered the final WIPS version. The distribution of the final 41 items in terms of item content was as follows: Behavioral intention -11 items, behavioral outcome -7 items, interpersonal attitude -5 items, (Jaksic & Schlegel, 2020) Ad-hoc rating task using video material of negotiation interactions…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, although we sought to cover a broad range of related constructs in our nomological networks throughout the studies, they clearly do not contain all possibly related constructs. For example, we had neither vocal emotional abilities ( Schlegel et al 2012 ), emotional knowledge ( Schlegel and Scherer 2018 ), emotional creativity ( Weiss et al 2023 ), deception detection abilities ( Wright et al 2012 ), nor the ability to judge other people’s emotions ( Jaksic and Schlegel 2020 ), just to name a few. However, with the emotion expression tasks presented in this study and the availability of the material, future studies will easily be able to fill these research gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Positive and negative emotions can be linked to chemical compositions. Moreover, investigations have shown that chemical composition impacts neural oscillation and, thus, electrical brainwave production [20] because emotions are contained in chemical compositions that impact electrical brain activity directly, they may be categorized using statistical features of the brainwaves generated, according to this study.…”
Section: B Eeg Brainwave Dataset: Feeling Emotionsmentioning
confidence: 99%